A study on syntactic, lexical-semantic and rhetorical features Of word groups containing words denoting seasons in vietnamese And english (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is a contrastive analysis of word groups containing words denoting seasons (WGCWSs) in Vietnamese and English. This thesis focuses on the syntactic, lexical-semantic and metaphorical features of WGCWSs in Vietnamese and English. The data for analysis in this research are 800 samples of WGCWSs (400 in Vietnamese among them 200 samples containing word xuân, 200 samples containing thu and 400 in English: 200 containing spring, 200 containing autumn) collected from Vietnamese and English poems from print materials and Internet. The thesis is carried out by using the descriptive method to classify, describe and analyze WGCWSs in Vietnamese and English in terms of syntax, lexical-semantics, and metaphor. With data from poetry by famous writers in Vietnamese and English, the researcher tries to point out some similarities and differences in the use of WGCWSs in both Vietnamese and English. The findings, we show that there are many differences in syntactic, semantic features and especially in metaphor. The word groups containing word denoting season in Vietnamese imply a lot of meanings. Finally, some practical implications in teaching, learning, and translating. The findings of the study are believed to benefit not only teachers of English and learners but also translators and those who are interested in linguistics and poetry.